Tool And Task Design Challenges For Left Handers: A Brief Review - Syed Mohamed, Muhammad Syafiq; Azani, Akmal Hafiz; Abdullah, Lokman; Zamri, Ruzaidi; Maslan, Mohd Nazmin; Mat Ali, Mahasan; Zainon, Maslan; Mohd Samsuddin, Noorazizi (Human Factors And Ergonomics Society Malaysia (HFEM), 2019)
Left-handed users are often overlooked by equipment and hand tool designers. Designers may assume that left handers will eventually learn to adapt themselves in a right-handed environment. However in reality left handers face a lot of difficulties when trying to perform tasks meant for right-handed users. Medical personnel are most affected by this issue, followed by workers in non-medical field such as services and manufacturing. This review aims to highlight the issues faced left handers by analysing common household product examples as well as hand tools in occupational settings. Discussions are centred on the differences between the right-handed tools versus left-handed tools, as well as task/procedural challenges faced by left handers. In summary, the notion of designing an ambidextrous tool may not be a realistic recommendation for tool manufacturers and designers.